Workshop Penyusunan Regulasi Pembentukan ULP Dan Regulasi Pedoman Pelaksanaan Pengadaan Barang/Jasa - Meinarni Asnawi (The Community Engagement Journal, 2018)
This community engagement activity is concerning workshop on the preparation of regulations for the establishment of procurement service units and regulations on the implementation guidelines for the procurement of goods/services in Papua Province. The regulatory workshop is expected to facilitate and smooth the work process of procurement service unit and other related parties as the provider of goods and service providers both in the process of accountability and monitoring and evaluation of goods and services provider activities. The participants of this activity are around 85 people. Then, the result of this activity is expected in preparing regent regulation concerning establishment of service/procurement service unit from each regency and follow-up in the form of socialization in each regency in Papua Province.